Pendampingan Pembuatan Kemasan Produk untuk Meningkatkan Penjualan UMKM Kacang Sangrai di Desa Kalitimbang Cilegon - Salsabila Maschaolah; Chandra Dewa; Anita Nurbayanti; Tiara Nofiana; Slamet Gunadi; Yolla Sukma Handayani; Asih Setyo Rini (Jurnal Kabar Masyarakat, 2024)
Micro, small and medium enterprises (MSMEs) often face the problem of simple packaging. It needs to be recognized that products made by MSMEs are better than products made by manufacturers. However, the packaging is not attractive because the MSME products are simple. This is the reason why MSME products have limited market reach and are difficult to compete in the market, especially in modern markets. The method of implementing the Food Product Packaging Assistance activities in Kalitimbang Village uses the method of discussion, face-to-face and providing direct counseling and direct practice. The implementation of training on July 27, 2024 was in the form of providing material on good packaging procedures provided by one of Bina Bangsa University's KKM students. The session length was approximately 15 minutes which was attended by several workers and MSME owners. Implementation of practical training and tutorials on how to package attractively. By using a standing pouch and labeling the packaging. By using standing pouches and labels on this packaging itself allows MSME players to save more time and be more practical and fast in packaging these products.